Larval digestion of different manure types by the black soldier fly (Diptera: Stratiomyidae) impacts associated volatile emissions. (April 2018) - Beskin, Kelly V.; Holcomb, Chelsea D.; Cammack, Jonathan A.; Crippen, Tawni L.; Knap, Anthony H.; Sweet, Stephen T.; Tomberlin, Jeffery K.
Highlights: A novel method of odor reduction for waste management is proposed. Select odorous VOCs were reduced by greater than 87% across three manure types by BSFL. Decrease in volatile emissions may be feed rate and manure type dependent. Abstract: Volatile emissions from decomposing animal waste are known environmental pollutants. The black soldier fly, Hermetia illucens (L.), is being evaluated for industrialization as a means to recycle wastes and produce protein for use as food and feed. We examined the ability of black soldier fly larvae to reduce odorous compounds associated with animal wastes. Black soldier fly larvae were reared under laboratory conditions on poultry, swine, and dairy manure at feed rates of 18.0 and 27.0 g every other day until 40% reached the prepupal stage. Volatile emissions were collected and analyzed from freshly thawed as well as the digested waste when 90% of the black soldier fly larvae reached the prepupal stage. Volatiles were also collected simultaneously from manure not inoculated with black soldier fly larvae (non-digested) and held under similar conditions. Manure samples were analyzed for relative amounts of nine select odorous volatile organic compounds: phenol, 4-methylphenol, indole, 3-methylindole, propanoic acid, 2-methylpropanoic acid, butanoic acid, 3-methylbutanoic acid and pentanoic acid. Black soldier fly larvae reduced emissions of all volatile organic compounds by 87% or greater. Complete reductions were observed for 2-methly propanoic acid in digested poultry manure, phenol, 4-methylphenol, indole and all five fatty acids in digested swine manure, and 4-methylphenol, indole, 3-methylindole and all five acids in digested dairy manure. This study is the first to identify volatile emissions from manure digested by black soldier fly larvae and compare to those found in non-digested manure. These data demonstrate additional benefits of using black soldier fly larvae as a cost-effective and environmentally friendly means of livestock manure management in comparison to current methods. Capsule: Black soldier fly larvae are capable of altering the overall profile of volatile organic compounds and reducing levels of targeted odorous compounds in livestock manure.